STRATEGI PENYELESAIAN PEMBIAYAAN BERMASALAH PADA AKAD MUDHARABAH DI BANK MUAMALAT INDONESIA SERTA PENGARUHNYA TERHADAP PENURUNAN TINGKAT NON PERFORMING FINANCING (NPF) BANK MUAMALAT INDONESIA - Lestari, Nur Melinda; Wati, Setia (Ekonomi Islam, 2018)
The author conducts the research within the scope of the Troubled Financing Settlement Strategy on Mudharabah Agreement at Bank Muamalat Indonesia. Problem financing is a problem that is very influential on bank soundness and almost occur in some banks, not to mention the Bank Muamalat Indonesia classified as experiencing problematic financing sufficient to the spotlight in the 2014 period of 6.55% and 2015 of 7.11%. Facts prove that in 2016 Bank Muamalat Indonesia able to reduce the level of problem financing to 3.83% and in 2017 to 4.7% thus proving that in fact Bank Muamalat Indonesia able to complete financing problem well in the next year with the strategy of financing problem settlement Bank Muamalat Indonesia conducted in the year 2016. However, the current discourse of Bank Muamalat will be acquired by Minna Padi securities company due to lack of capital faced by Bank Muamalat Indonesia caused by high NPF (Non-Performing Finance) factor, more or less influenced by problematic financing including mudharabah financing. This study aims to determine the strategy of financing settlement on mudharabah contract. The results of this study show that in the handling of customers who experienced problematic financing, Bank Muamalat Indonesia using the strategy, revitalization: rescheduling, reconditioning, restructuring and management assistance, then if the customer is not well-settled then the Settlement is settled through the guarantee, Through BAMUI (Arbitration Board Muamalat Indonesia), and settlement by way of Litigation. The results of this study are expected to provide input to the high NPF (Non-Performing Finance) issues currently facing Bank Muamalat Indonesia and target the NPF to fall to 3%.